2018
DOI: 10.1073/pnas.1801238115
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic analysis of social-class mobility in five longitudinal studies

Abstract: SignificanceGenome-wide association study (GWAS) discoveries about educational attainment have raised questions about the meaning of the genetics of success. These discoveries could offer clues about biological mechanisms or, because children inherit genetics and social class from parents, education-linked genetics could be spurious correlates of socially transmitted advantages. To distinguish between these hypotheses, we studied social mobility in five cohorts from three countries. We found that people with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
274
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 280 publications
(294 citation statements)
references
References 66 publications
15
274
1
4
Order By: Relevance
“…For example, in a large‐scale GWAS conducted by Lee et al, an EA PGS accounted for 11% to 13% of the variance in years of schooling among European descent individuals compared with 1.6% of the variance among socioeconomically diverse individuals of African descent (net attenuation ~85%). Other work conducted by Belsky et al found that an EA PGS accounted for a similar level of variance in educational attainment among individuals of European heritage, with a significant reduction in the variance accounted for among individuals of African heritage with diverse socioeconomic standing. Although these studies suggest that polygenic contributions to educational attainment and post‐secondary education status are reduced when considering socioeconomically diverse African American populations, it is unclear whether these findings would apply to a low‐income, African American sample.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…For example, in a large‐scale GWAS conducted by Lee et al, an EA PGS accounted for 11% to 13% of the variance in years of schooling among European descent individuals compared with 1.6% of the variance among socioeconomically diverse individuals of African descent (net attenuation ~85%). Other work conducted by Belsky et al found that an EA PGS accounted for a similar level of variance in educational attainment among individuals of European heritage, with a significant reduction in the variance accounted for among individuals of African heritage with diverse socioeconomic standing. Although these studies suggest that polygenic contributions to educational attainment and post‐secondary education status are reduced when considering socioeconomically diverse African American populations, it is unclear whether these findings would apply to a low‐income, African American sample.…”
Section: Introductionmentioning
confidence: 75%
“…While our work is a first step in identifying whether polygenic propensity for educational attainment is associated with higher education status in non‐European samples, our results do not imply a causal relationship between genes and behavior. In support of this idea, recent work indicates that parents' polygenic propensity for educational attainment influences their children's educational attainment through parents (a) transmitting their own genetics to their children, and (b) shaping the environments in which their children grow up in . In terms of the former, recent work by Belsky et al found that individuals with a higher EA PGS tended to have higher levels of education and occupational status and come from socioeconomically advantaged families.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of 10 PCs was based on our reading of the literature and current best practices (Conley et al, 2016;Price et al, 2006;Price, Zaitlen, Reich, & Patterson, 2010), the meta-analysis which also adjusted for 10 PCs (Yengo et al, 2018), as well as recent work using Add Health genetic data (Belsky et al, 2018). PCs were calculated for nonrelated individuals of European ancestry using the -pca command in PLINK and based on a set of pruned SNPs where linkage disequilibrium pruning was conducted using a window size of 50 kb, a step of five variants, and an R-square cutoff of 0.2.…”
Section: Ancestry-specific Pcsmentioning
confidence: 99%